An Empirical Study to Examine Transaction Costs Emerging in Strategic Airline Alliances - Bıyıklı, Fatih; Özkara, Belkıs (Journal of Applied And Theoretical Social Sciences, 2023)
Airline firms are aimed to create alliances to decrease operational costs and increase flight networks to benefit from economies of scale, scope and density. However, most of the firms involved in airline alliances, on the one hand, decrease the flight costs, but on the other hand, they have to deal with unpredicted transaction costs. In the scope of this study, 59 airline businesses involved in one of the global airline alliances have been investigated through the transaction cost approach. The research was conducted with 85 middle and top-level managers of global airline alliance businesses, and data was collected through an online survey. Data were analyzed using the PLS-YEM program within the framework of the theoretical model created with partner trustworthiness, opportunistic behaviour and alliance outcome. The hypotheses constructed were tested using the structural equation model according to the structure of the data. As a result of the analysis, it was concluded that all the basic assumptions of the transaction cost approach were supported. It was found that the partner reliability variable gave a statistically significant result in estimating the opportunistic behaviour and the opportunistic behaviour in predicting the cooperation outcome.